Genexpert test and endometrial histological findings in infertile women - Garg, Roopakshi; Agarwal, Neelima; Gupta, Manisha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Infertility is a worldwide health problem with very definite physiological, psychological and social implications. According to studies, about 30% of infertility cases are due to the male factors, 40 to 50% have the origin of female factors and 20 to 30% of cases are caused by both male and female factors. Genital tuberculosis is among the main causes of female infertility. Due to its high prevalence, especially in developing countries, work-up of an infertile couple should include evaluation for tuberculosis irrespective of history or exposure. The objective of the present study is to find out the prevalence of genital tuberculosis in all females presenting with infertility in a tertiary care hospital over a given period of time, and diagnostic comparison of endometrial tuberculosis by GeneXpert and Histopathological examination (HPE). Methods: The prospective observational study was conducted from January 2016-June 2017.A total of 81 endometrial tissue samples were collected from the women, satisfying the inclusion and exclusion criteria. Results: GeneXpert scored negative in our study. On HPE, out of 81 patients, proliferative endometrium (anovulatory) was found in 34 cases (41.9%), non-specific endometritis in 1 case (1.23%) and 1 case (1.23%) was found positive for tubercular endometritis. Secretory endometrium was found in 45 cases (55.55%). Conclusions: Endometrial biopsy shows not only the tuberculous endometritis, but also gives additional information about hormone response of endometrium, local factors of endometrium concerning non-specific and specific infections and anovulatory cycles. Gene Expert if positive on endometrial biopsy is a reliable test for FGTB and treatment can be started on its basis.